Peran APBD Terhadap Pertumbuhan ekonomi Daerah - FRAHMAWATI BLMULO (JURNAL LEGALITAS, 2009)
The isue of law act no 32 of the year 2004 has caused lack of synergy between regional council and the executive bodies. the lack of synergy is caused by the more power ti the executive compared to that oh the legislative. This article in addressing to see the role of APBD to growth of economics Desentralisasi fiscal has influence which are positive to growth of economics region, raising inflation rate region, cause of the happening of development difference between sub-provinces and town and would be more enjoyed by group of elite region, repair invesment climate in regency/town and province a real influential to growth of area economics for the purpose the role of APBD to growth of very important area economics.